How muslims trivialize the Qur'an - Hasan, Md. Mahmudul (Blog posting 20 October 2014, 2014)
The physical desecration of the Qur’an is a grave sin, but trivializing it is also a serious offence. Muslims certainly do not disrespect their holy book tangibly and physically. Their obvious reverence to the scripture and extreme caution when handling it are paradigmatic, as most of them wrap and place it on a raised surface in the house or in places of worship. However, they manifest, perhaps unaware, their conceptual irreverence for the sacred book in two ways: using it for lesser purposes and splitting it into pieces, which may amount to trivializing it.